Intersecting barriers to adolescents’ educational access during COVID-19: Exploring the role of gender, disability and poverty - Jones, Nicola; Tapia, Ingrid Sanchez; Baird, Sarah; Guglielmi, Silvia; Oakley, Erin; Yadete, Workneh Abebe; Sultan, Maheen; Pincock, Kate (Elsevier, 2022)
This article was published in International Journal of Educational Development [©2021 Published by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.ijedudev.2021.102428 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S073805932100081X?via%3Dihub